Tajikistan’s Winter Energy Crisis : Electricity Supply and Demand Alternatives - Fields, Daryl (World Bank, Washington, DC, 2014)
Reliable power supply is critical for Tajikistan's economy and poverty reduction goals. Without reliable, affordable electricity throughout the year, Tajikistan's businesses cannot invest, operate and create jobs; hospitals and schools cannot function fully or safely with frequent power cuts during winter; citizens suffer indoor air pollution from burning wood for heating and cooking. Electricity also powers the country's two largest exports: aluminum and agricultural produce, which account for about 30 percent of Tajikistan's annual gross domestic product and almost 45 percent of export earnings. Currently, electricity is the cheapest available resource to heat homes so the residential and commercial sectors are highly dependent on electricity for heat as well as lighting and industrial processes. The Government is responsible for guiding programs that keep power supply apace with demand. The purpose of this study is to assist the Government in further defining ways to meet growing demand for electricity in Tajikistan, with a particular focus on the recurring winter shortages which amount to about 24 percent of winter demand. The study also examines the potential benefits of power exports, particularly during summers when hydropower plants spill energy. The study explores a range of alternatives to meet electricity demand as quickly as possible and develop a short term plan of action to alleviate the social and economic costs of winter shortages. The study focuses on multiple initiatives that can be started immediately and simultaneously, and will establish fundamental components of energy security for Tajikistan, namely: to moderate unsustainable demand growth, protect the current asset base, and remedy the thermal/hydro imbalance in the energy sector.